2019
DOI: 10.5505/pajes.2019.88123
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Locations of Airports and Passenger Demand by Evaluating Accessibility and Special Properties: Case Study of Turkey

Abstract: ÖzThe accessibility of airports and the airport preference of users are significant criteria for the competitiveness of airports. When passengers choose a route, they actually expect the completion of the transportation chain and they want to travel to the door from the door. For this reason, the factors that affect the passenger's decision for a significant option go beyond the price and quality of air services. The decision for a specific air service and a particular airport depends on the accessibility of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…and the street design (all being supply), addressing to the attractiveness of walking through the design elements are assumed to be among the land use characteristics [32], [64]- [66]. But again, these are the supply elements of transport taken as proxy variables to land use, which are sometimes named as "land side" accessibility [67].…”
Section: Supply Variables Disrupted By Land Use Variables In Urban Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…and the street design (all being supply), addressing to the attractiveness of walking through the design elements are assumed to be among the land use characteristics [32], [64]- [66]. But again, these are the supply elements of transport taken as proxy variables to land use, which are sometimes named as "land side" accessibility [67].…”
Section: Supply Variables Disrupted By Land Use Variables In Urban Co...mentioning
confidence: 99%
“…Again, the transport supply and infrastructure variables such as paved roadways or parking areas should be separated from the other land use ones for obtaining undisrupted healthy results. This is because, though the former is used in the transport supply, the latter is used in the domain of land use in terms of design, land use mix, and density [59], [67] which should be looked in land use/transportation relationship area. Most of the times, in the literature, these are all mixed up, and supply is considered as capacity level only.…”
Section: Supply Variables Disrupted By Land Use Variables In Urban Co...mentioning
confidence: 99%
“…Only one study is found to have addressed accessibility to airports in Turkey ( 46 ), and it overlooked the realized accessibility problem by not taking into account road transport networks or airports’ activities. Therefore, the current study is the first attempt at measuring accessibility to Turkey’s entire domestic air travel network by combining land-based and air-based accessibility measures and investigating the change in spatial accessibility to airports over time.…”
Section: Literature Reviewmentioning
confidence: 99%